2021
DOI: 10.18483/ijsci.2485
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles and Health Promoting Uses of Carrot (Daucus carota L.) and Cucumber (Cucumis sativus L.)

Abstract: Humans are in-separately linked to the existence of vegetables, as they are the source of several bio-products essential for the survival of the animal kingdom. The importance of vegetables from the point of view of the food industry is determined by their complex chemical content that is important to the human body and this includes organic substances (lipids, proteins, carbohydrates and organic acids). This study examines comparatively the levels of lipid compositions in the samples of dried carrot (Daucus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Seeds are a rich source of bioactive phytosterols, such as radish seeds with good phytosterol profiles mainly consisting of brassicasterol, campesterol, and sitosterol [97]; however, considerable quantities of phytosterols are also reported in edible roots. A study has shown 366.16 mg/100 g phytosterol content in carrots with campesterol and sitosterol as major constituents [98]. Radish sprouts also have shown campesterol (947 μg/g) and β-sitosterol (899 μg/g) in considerable amounts [99].…”
Section: Other Bioactive Compoundsmentioning
confidence: 99%
“…Seeds are a rich source of bioactive phytosterols, such as radish seeds with good phytosterol profiles mainly consisting of brassicasterol, campesterol, and sitosterol [97]; however, considerable quantities of phytosterols are also reported in edible roots. A study has shown 366.16 mg/100 g phytosterol content in carrots with campesterol and sitosterol as major constituents [98]. Radish sprouts also have shown campesterol (947 μg/g) and β-sitosterol (899 μg/g) in considerable amounts [99].…”
Section: Other Bioactive Compoundsmentioning
confidence: 99%
“…Carrots contain carotenoids, flavonoids, polyacetylenes, vitamins, and minerals, all of which have many nutritional and health benefits. Carrots are rich in beta-carotene, ascorbic acid, iron, calcium, phosphorus, folic acid, B vitamins, vitamin C and Vitamin E, and high fiber, carotenoids, and phenolic compounds antioxidants, anti-carcinogenic, and immune [15] [16].…”
Section: M D Utamimentioning
confidence: 99%